2011
DOI: 10.5194/acp-11-10965-2011
|View full text |Cite
|
Sign up to set email alerts
|

Parameterisation and impact of aerosol uptake of HO<sub>2</sub> on a global tropospheric model

Abstract: Abstract. HO 2 is an important atmospheric trace gas, whose sink to aerosol is poorly understood yet significant. Previous parameterisations of the rate of uptake have been limited by the lack of laboratory studies. This paper creates a parameterisation for γ HO 2 based on the available laboratory studies. The calculated global mean γ HO 2 is 0.028, significantly lower than previous work (0.2). Modelled concentrations of HO 2 show significant regional sensitivity to the value of γ HO 2 (up to +106 % at the sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 36 publications
4
39
0
Order By: Relevance
“…At RH relevant to the lower stratosphere (<40%) the measurements showed that γ (HO 2 ) is in the range 0.020-0.028 at 295 K. An inverse temperature dependence of γ (HO 2 ) onto dry seasalt aerosols has previously been observed (Remorov et al, 2002); although there have been no systematic experimental studies of the temperature dependence of γ (HO 2 ), parameterisations have developed (Thornton et al, 2008;Macintyre and Evans, 2011). At stratospherically relevant temperatures (T = 200-220 K), γ (HO 2 ) is likely to be considerably larger than observed at 295 K; however it is not possible to cool the aerosol flow tube/SMPS system to verify this experimentally.…”
Section: Comparison Of γ (Ho 2 ) With Literature Valuesmentioning
confidence: 99%
“…At RH relevant to the lower stratosphere (<40%) the measurements showed that γ (HO 2 ) is in the range 0.020-0.028 at 295 K. An inverse temperature dependence of γ (HO 2 ) onto dry seasalt aerosols has previously been observed (Remorov et al, 2002); although there have been no systematic experimental studies of the temperature dependence of γ (HO 2 ), parameterisations have developed (Thornton et al, 2008;Macintyre and Evans, 2011). At stratospherically relevant temperatures (T = 200-220 K), γ (HO 2 ) is likely to be considerably larger than observed at 295 K; however it is not possible to cool the aerosol flow tube/SMPS system to verify this experimentally.…”
Section: Comparison Of γ (Ho 2 ) With Literature Valuesmentioning
confidence: 99%
“…To investigate both the impact of the uptake and whether H 2 O 2 is produced, three simulations are run, (i) with no cloud uptake of HO 2 , (ii) with cloud uptake (an assumed pH of 5) of HO 2 using the Thornton mechanism to produce H 2 O 2 , and (iii) with cloud uptake (assumed pH of 5) of HO 2 to produce H 2 O. All simulations include HO 2 uptake onto aerosol with γ HO 2 of 0.2, which is the standard value used in GEOS-Chem (Martin et al, 2003;Macintyre and Evans, 2011). Figure 10 shows the annual fractional change in surface HO 2 , OH, H 2 O 2 and O 3 concentrations with cloud uptake switched on, and with H 2 O 2 being either produced or not.…”
Section: Global Impact Of the Uptake Of Ho 2 Onto Cloud Dropletsmentioning
confidence: 99%
“…The general consensus, until recently, was that these reactions would ultimately produce H 2 O 2 (Jacob, 1996), but the significance of the reactions depends critically on whether this is the case or whether, instead, H 2 O is produced (Macintyre and Evans, 2011). This is significant, as H 2 O 2 can photolyse to return odd hydrogen (HO x = OH + HO 2 ) to the gas phase, whilst cloud uptake of HO 2 to form H 2 O provides a terminal sink for HO x .…”
Section: Introductionmentioning
confidence: 99%
“…For HO 2 , γ HO 2 = 0.028 is used based on the mean value reported by the parameterisation by Macintyre and Evans (2011). For NO 3 , a value of γ NO 3 = 0.001 is used.…”
Section: Model Approachmentioning
confidence: 99%